If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (r + -6) = (3r + -3) Reorder the terms: (-6 + r) = (3r + -3) Remove parenthesis around (-6 + r) -6 + r = (3r + -3) Reorder the terms: -6 + r = (-3 + 3r) Remove parenthesis around (-3 + 3r) -6 + r = -3 + 3r Solving -6 + r = -3 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. -6 + r + -3r = -3 + 3r + -3r Combine like terms: r + -3r = -2r -6 + -2r = -3 + 3r + -3r Combine like terms: 3r + -3r = 0 -6 + -2r = -3 + 0 -6 + -2r = -3 Add '6' to each side of the equation. -6 + 6 + -2r = -3 + 6 Combine like terms: -6 + 6 = 0 0 + -2r = -3 + 6 -2r = -3 + 6 Combine like terms: -3 + 6 = 3 -2r = 3 Divide each side by '-2'. r = -1.5 Simplifying r = -1.5
| 20x+5-30x=182 | | 120/360=x/100 | | c=30.25-0.06x | | 4x+12=-19-4x | | 2x-9-11=10 | | x+1.9x=29000 | | 9x^2-54x+40=0 | | F(x)=3x-2/√x | | y=0.9x+x | | 2x(x-4)=42 | | .4y=3x-7 | | v/136=17 | | b/9=1025 | | x-35.9=-55.6 | | 4x-9=10x+35 | | y/5.2=30 | | e^5x+2=p | | 11/15z=1/6-14/5 | | 23d=966 | | 5/7w=45 | | 7n^2-7=56 | | 1/15=x/35 | | 2b+24b+54=0 | | 456r=1368 | | 3y^2+6x=12 | | 5x+13-9x=16-19x+15x-3 | | 5x^2+25k-25=0 | | 2w^2=98 | | 2x^4-81x^2=0 | | q=50+0.5p | | 58-w=246 | | q=50+0.5 |